Late development of multiple supernumerary teeth in a patient with hypodontia - Stefański, Tomasz; Postek-Stefańska, Lidia; Iwanecka-Zduńczyk, Maria (Journal of Stomatology, 2019)
Hypo-hyperdontia is a very rare condition in which dental agenesis and supernumerary tooth (or teeth) occur concomitantly. The present case report describes late-forming multiple supernumerary teeth in all quadrants in a nonsyndromic boy with a radiographic diagnosis of mandibular incisor hypodontia made when the patient was 9 years of age. Developing supernumeraries were detected after uneventful orthodontic treatment using fixed appliances on a panoramic radiograph taken shortly after debonding at the age of 15. Cone beam computed tomography was performed to determine the exact location of the extra teeth relative to normal dentition and identify possible root resorption. To the best knowledge of the authors, this is the first reported case of late-developing supernumeraries being a part of the hypo-hyperdontia condition. In conclusion, general dental practitioners should be aware of the rare possibility that a generally healthy individual may develop multiple supernumerary teeth even with the previous diagnosis of hypodontia.